BROTOPENTECOSTALISMO: A RELIGIOSIDADE NEGRA DA PERIFERIA BRASILEIRA - UM ESTUDO DA PERIFERIA URBANA DA REGIÃO METROPOLITANA DE JOÃO PESSOA - FLORES FILHO, JOSÉ HONÓRIO (2017)
This study analyzes a phenomenon Pentecostal that expands in the peripheries and favelas of Brazil and that we call brotopentecostalism. This Pentecostalism has as characteristic, to be a movement with important participation of blacks. As the peripheries and favelas are mainly black, these were affiliated with candomblés and umbandas, that once dominated these areas. With the arrival and proliferation of Pentecostalism, the Afro-Indo-Brazilian religions lost ground. Many blacks living in these areas of favelas were converted by the Pentecostal movement, but this Pentecostalism changed, became more diverse and assumed the popular characteristics of Brazilian black culture. In this transition, a metamorphosis of an official protopentecostalism, more solidified in their organizations, towards a more fluid Pentecostalism occurred, with churches generally constructed of fast and precarious form and, generally, of short duration. In these spaces, musicality through percussions, ginga, freedom of movement and ecstasy of the Holy Spirit, appeared as a reinterpretation of the African trance. The fact made the Pentecostal movement the proper vehicle for black. This question is based on Bastide and his studies on black and his Afro-Brazilian religion. On the question of popular religiosity, this research finds reference in Carlos Brandão. Based on the concept of coercion and emblematic cohesion are the Bourdian concepts of habitus and symbolic violence, as well as the geertian concept of religion as a symbolic system. The present thesis takes into account the real conditions of existence of the black Pentecostals marked by high social vulnerability. We searched two peripheral areas of the Metropolitan Region of João Pessoa: Mandacarú (Mandacarú and Alto do Céu) in João Pessoa and Mutirão (Mário Andreazza and Comercial Norte) in Bayeux. Populations in these areas are mostly black, poor housing and a high unemployment rate. However, there is an expressive presence of Pentecostal churches, this makes these institutions present themselves as important generators of opportunity structure and social capital. And this occurs as a typical determinant element of affirmation of brotopentecostal identity, and of popular religious movement reactive to the adverse conditions of social vulnerability and segregation in peripheries and favelas. The objective of the research was to analyze the relationship between brotopentecostalism as a typical popular religion of periphery, segregation, social vulnerability and identity in the reality of black brotopentecostal. The research methodology was quantitative-qualitative, including bibliographic, ethnographic, participatory observation, questionnaire application and in-depth interviews. The participants of the research were white and black brotopentecostais in their various hierarchical religious degrees, all of them residents of the urban periphery of João Pessoa and followers of Pentecostal churches that act in that context.